1995
DOI: 10.1248/bpb.18.933
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Polyacetylenic Alcohols in Crude Drugs Using the ELISA for Panaxytriol.

Abstract: Polyacetylenic alcohols such as panaxytriol, panaxynol and panaxydol isolated from the roots of Panax ginseng C. A. MEYER have antiproliferative activity against various cultured tumor cells. Anti-panaxytriol antibody was obtained by immunizing rabbits with panaxytriol-bovine serum albumin conjugates. Although the antibody reactivity was directed mainly toward panaxytriol, there was a slight cross-reactivity with other polyacetylenic compounds. The antibody was, therefore, used for screening a large number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Other isolated polyacetylenic alcohols-panaxynol (6) and heptadeca-1,8-diene-4,6-diyne-3,10-diol (20) (Saposhnikoviae radix: Fang Feng in Chinese Medicine) and falcarindiol (21) (from Peucedani radix, Qian Hu), 9,10-epoxy-16-hydroxy-octadeca-17-ene-12,14-diyne-1-al (22) (from Foeniculi fructus, bitter fennel) as well as panaxydol 5, panaxynol (6), and panaxytriol (7) (from Panax ginseng)-inhibited the growth of cells from a human gastric adenocarcinoma cell line, MK-1, in a dose-dependent manner (48)(49)(50)(51).…”
Section: Acetylenic Metabolites From Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other isolated polyacetylenic alcohols-panaxynol (6) and heptadeca-1,8-diene-4,6-diyne-3,10-diol (20) (Saposhnikoviae radix: Fang Feng in Chinese Medicine) and falcarindiol (21) (from Peucedani radix, Qian Hu), 9,10-epoxy-16-hydroxy-octadeca-17-ene-12,14-diyne-1-al (22) (from Foeniculi fructus, bitter fennel) as well as panaxydol 5, panaxynol (6), and panaxytriol (7) (from Panax ginseng)-inhibited the growth of cells from a human gastric adenocarcinoma cell line, MK-1, in a dose-dependent manner (48)(49)(50)(51).…”
Section: Acetylenic Metabolites From Plant Speciesmentioning
confidence: 99%
“…These compounds are characterized by the presence of a diacetylenic carbinol and an α-acetylenic carboxylic acid. Osirisynes A-F exhibited moderate cytotoxicity against a human leukemia cell-line (KS62), with LC 50 values of 25,48,52,25,20, and 22 µM for 216-221, respectively. In addition, 218, 220, and 221 inhibited Na + /K + -ATPase and reverse transcriptase at concentrations of l µg/mL.…”
Section: Marine and Freshwater Sponges (Porifera)mentioning
confidence: 99%
“…Ginseng protects the cardiovascular system, stimulates the central nervous system [1] and possesses anti-cancer activities [2,3] inhibiting human gastric adenocarcinoma [4] and human breast carcinoma [5]. Therefore, ginseng is a potential cancer preventive agent [6].…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, we took note of the disclosure of a series of biologically active polyacetylene natural products isolated from the P. ginseng root. We were originally drawn, in particular, to (3R, 9R, 10S)-panaxytriol (PXT) (16) on the basis of reports of its in vitro cytotoxic activity against a range of human tumor cells, including breast carcinoma (breast M25-SF) (17) and gastric carcinoma (MK-1) (18). In one in vivo study, PXT was reported to suppress the growth of B16 melanoma cells in mouse models (19).…”
mentioning
confidence: 99%